Menggali Kearifan Lokal Sebagai Sumber Dukungan Psikologis: Pendekatan Budaya Dalam Promosi Kesehatan Mental Komunitas di Desa Gantang Rani - Meri Hafni; Farida Hanum Siregar; Syafrizaldi (LPPI UMN AL WASHLIYAH, 2025)
This community service activity aims to improve the mental health of the people in Gantang Tani Village by utilizing local wisdom as a psychological resource that aligns with the cultural values and norms of the area. This agricultural village still maintains a strong traditional value system. Using a participatory approach through observation, interviews, FGD, and training for local facilitators, this activity explores cultural practices such as marsialapari (cooperation), manortor (traditional dance), customary rituals, and local proverbs in strengthening the psychological resilience of the community. The findings show that local wisdom can enhance a sense of solidarity, regulate emotions, and reduce collective pressure. The main issue is the cultural potential that has not yet been fully maximized as a psychological resource. This program fosters a new awareness of the significance of mental health within the cultural context. Suggestions include the integration of cultural values in psychological counseling, the development of locally-based mental health promotion modules, and the involvement of traditional leaders. This activity also produces a model of the village cultural calendar to support the mental well-being of the community. Overall, this service illustrates that culturally-based interventions have great potential in supporting mental health in rural communities in an inclusive and sustainable manner.